Bacterial vaginosis among women at high risk for HIV in Uganda: high rate of recurrent diagnosis despite treatment. (7th August 2015) - Francis, Suzanna C; Looker, Clare; Vandepitte, Judith; Bukenya, Justine; Mayanja, Yunia; Nakubulwa, Susan; Hughes, Peter; Hayes, Richard J; Weiss, Helen A; Grosskurth, Heiner
Abstract : Objectives: Bacterial vaginosis (BV) is associated with increased risk for sexually transmitted infections (STIs) and HIV acquisition. This study describes the epidemiology of BV in a cohort of women at high risk for STI/HIV in Uganda over 2 years of follow-up between 2008–2011. Methods: 1027 sex workers or bar workers were enrolled and asked to attend 3-monthly follow-up visits. Factors associated with prevalent BV were analysed using multivariate random-effects logistic regression. The effect of treatment on subsequent episodes of BV was evaluated with survival analysis. Results: Prevalences of BV and HIV at enrolment were 56% (573/1027) and 37% (382/1027), respectively. Overall, 905 (88%) women tested positive for BV at least once in the study, over a median of four visits. Younger age, a higher number of previous sexual partners and current alcohol use were independently associated with prevalent BV. BV was associated with STIs, including HIV. Hormonal contraception and condom use were protective against BV. Among 853 treated BV cases, 72% tested positive again within 3 months. There was no difference in time to subsequent BV diagnosis between treated and untreated women. Conclusions: BV was highly prevalent and persistent in this cohort despite treatment. More effective treatment strategies are urgently needed.